Transgenic flavonoid tomato intake reduces C-reactive protein in human C-reactive protein transgenic mice more than wild-type tomato - Sonnewald, Uwe; et al. (Journal of Nutrition, 2006)
The increased consumption of fruits and vegetables is associated with reduced cardiovascular disease. The molecular basis of this health effect is not fully understood, yet dietary flavonoids are thought to play an important role. Genetic engineering has enabled us to overexpress specific flavonoids (flavones and flavonols) in tomato fruit. Human C-reactive protein transgenic (CRPtg) mice express markers of cardiovascular risk that allow us to study of the putative health effects of wild-type tomato (wtTom) and flavonoid-enriched tomato (flTom). In this study, we analyzed whether consumption of wtTom, at a dose achievable with a human diet, has beneficial effects on cardiovascular risk markers and whether flTom may enhance such effects. CRPtg mice were fed a diet containing 4 g/kg wtTom, flTom peel, vehicle, or 1 g/kg fenofibrate, which reportedly reduces cardiovascular risk, for 7 wk. Markers of general health (bodyweight, food intake, and plasma alanine aminotransferase activities) and of cardiovascular risk (plasma CRP, fibrinogen, E-selectin, and cholesterol levels) were analyzed. All groups had comparable food intakes and body-weight gains. Plasma alanine aminotransferase activities increased significantly in vehicle and fenofibrate-treated mice. Compared with baseline, wtTom and fITom significantly reduced basal human CRP concentrations by 43 and 56%, respectively. The CRP-lowering effect of flTom significantly exceeded that of wtTom. The effects of flTom on CRP were reversed within a 2-wk washout period. WtTom and flTom did not affect fibrinogen, but comparably repressed E-selectin expression and upregulated HDL cholesterol. Tomato peel consumption improved cardiovascular risk factors in CRPtg mice, a beneficial effect that was further enhanced by enrichment of the flavonoid content.